A Comparative Study of Penicillin G Acylase Expression in Two Escherichia coli Strains: BL21 (DE3) and Arctic Express - Cendana, Kartika Sari; Wulandari, Sri Rezeki; Sabbathini, Gabriela Christy; Ulfah, Maria; Achnafani, Dini; Abinawanto; Aniqah, Sunni Sofiah; Helianti, Is; Nurhayati, Niknik (HAYATI Journal of Biosciences, 2026)
The growing demand for semisynthetic beta-lactams has directed attention towards enzymes, specifically Penicillin G Acylases (PGAs), for their potential in synthesizing these antibiotics. This study delves into the expression of Achromobacter xylosoxidans PGA (AxPGA) in Escherichia coli, with a focus on enhancing the yield of active PGA, often constrained by a complex maturation process. The optimization of PGA expression included variations in IPTG concentration and the addition of CaCl2. Furthermore, the study compared PGA expression in E. coli BL21 (DE3) with that in E. coli Arctic Express (DE3), capable of co-expressing chaperones (chaperonin Cpn60 and Cpn10). Induction with 0.5 mM IPTG resulted in the highest hydrolytic activity in both strains, with Arctic Express (AE) exhibiting significantly higher activity due to improved folding facilitated by cold-adapted chaperonins. Alongside optimal IPTG induction, the addition of 10 mM CaCl2 in the culture media significantly increased PGA activity in both strains, highlighting that Ca2+ supplementation is an effective strategy to enhance the yield of functional PGA. Subcellular fractionation demonstrates that the periplasmic fraction yielded higher volumetric and specific activities compared to the cytoplasmic fractions in both E. coli strains, highlighting the importance of periplasmic processing for PGA maturation. This suggests that extracting the periplasmic fraction is an effective strategy for recovering active PGA while avoiding or reducing contamination either from co-expressed cytoplasmic chaperones or other intracellular proteins. These findings emphasize that induction strategy, ionic stabilization, and host strain selection play synergistic roles in increasing active recombinant PGA expression.